Changes in Mitochondrial Electron Partitioning in Response to Herbicides Inhibiting Branched-Chain Amino Acid Biosynthesis in Soybean - Gaston, Susana (The American Society for Plant Biologists, 2003)
The adaptation of the respiratory metabolism in roots of soybean (Glycine max L. Merr. cv Ransom) treated with herbicides that inhibit the enzyme acetolactate synthase (ALS) was analyzed. A new gas phase dual-inlet mass spectrometry system for simultaneous measurement of (34)O(2) to (32)O(2) and O(2) to N(2) ratios has been developed. This system is more accurate than previously described systems, allows measurements of much smaller oxygen gradients, and, as a consequence, works with tissues that have lower respiration rates. ALS inhibition caused an increase of the alternative oxidase (AOX) protein and an accumulation of pyruvate. The combination of these two effects is likely to induce the activation of the alternative pathway and its participation in the total respiration. Moreover, the start of the alternative pathway activation and the increase of AOX protein were before the decline in the activity of cytochrome pathway. The possible role of AOX under ALS inhibition is discussed.